REVIEW OF INVENTIONS IN THE FIELD OF NEUROCYBERNETICS AND NEUROMODELLING - Saveliev, A. V. (Radio Electronics, Computer Science, Control, 2024)
In the article the results of same works on neurocybernetics and neural computers directions was implemented by author since 1977 from items of them embodiment in the inventions series protected by the patents are briefly submitted. They are: the research of wave conduction on dendrites, dendral processors; dynamic simulation of neural system; research of cycles in neural system and reverberationary models; research of post-tetany potentiation and memory mechanisms; research of chaotic modes in neurons and neural networks; learning of neuronic logic; research of coding mechanisms in neural system, simulation of pessimum phenomenon and rhythm transformation; development and using of neural network concept of neuron.